P3 12 More Star Wars? We are all Doonium-ed! - Brewer, Lois; Bates, Ethan; Sadler, Tommy; Smith, Kennedy (Physics Special Topics, 2022)
In our previous paper, we discussed which of our chosen materials was most similar to Doonium [1]. Here, we build upon this paper, using the suggested improvements to establish a more accurate picture. Using the iconic scene from The Phantom Menace, where Qui-Gon Jinn cuts through the door with his green lightsaber in 14s [2], we find that aluminium most closely resembles Doonium, taking 13.8s to cut through the door, compared to 29.8s for titanium and 39.6s for carbon steel.